Utilization of Various Diluents on the Quality of Frozen Semen from Saanen Goats - Nisfimawardah, Lailatun; Husein, Firdaus; Astuti, Erlina; Monasdir, Monasdir; Riskayanti, Riskayanti; Nugroho, Antonius Adhityawan (JURNAL ILMIAH PETERNAKAN TERPADU, 2025)
Saanen goats have low semen volume per ejaculation but high concentration. This study was conducted at the Singosari Center Artificial Insemination (SCAI), Malang Regency, East Java. The purpose of this study was to determine the effect of using various diluents on the quality of Saanen goat semen. The samples used consisted of 3 male Saanen goats with body weights of 32.5 kg, 43 kg and 44.5 kg with ages of 1.5-2 years. The use of various different diluents consisted of tris aminomethane egg yolk diluent (Treatment 0), AndroMed® (Treatment I) and OvixCell® (Treatment II). The research method used a laboratory experimental method using a Randomized Block Design (RAK). Data analysis using Analysis of Variance (ANOVA) if there is a significant or very significant difference then further analysis using Duncan's Multiple Range Test. The results showed that the use of various different diluents had no significant effect (P>0.05) on motility, viability and spermatozoa abnormalities. The research variables included volume, color, pH, odor, consistency, spermatozoa concentration, motility, viability and abnormality. The results showed that the use of various diluents was feasible to be used as diluents and was able to maintain normal motility>40%, spermatozoa survival and abnormality (<5%) against semen freezing.